QUALITY PRESERVATION OF ‘LAETITIA’ PLUMS IN ACTIVE MODIFIED ATMOSPHERE STORAGE - STANGER,MAYARA CRISTIANA (2017)
ABSTRACT Recent studies have shown that passive modified atmosphere storage (MA) delays the ripening of ‘Laetitia’ plums but it increases the incidence of internal browning in comparison to cold storage (CS), possibly due to high CO2 and/or ethylene accumulation inside the package. The aim of this study was to evaluate the effect of active MA conditions [LDPE film (40 µm)] with CO2 absorber combined with low ethylene (LE) on ripening and quality preservation of ‘Laetitia’ plums during storage at 0.5ºC±0.1ºC and RH of 96%±2%. The treatments evaluated were cold storage (CS; 21.0 kPa O2 + <0.03 kPa CO2); nonperforated MA with CO2 absorber; non-perforated MA with CO2 absorber and LE; perforated MA (with two perforations with diameter = 0.5 mm) with CO2 absorber; and perforated MA with CO2 absorber and LE. The partial pressures of O2 + CO2 (kPa) were 1.2 + <0.1 and 2.8 + <0.1, in non-perforated and perforated MA, respectively. Active MA, mainly non-perforated package, with CO2 absorber and LE, delayed fruit ripening, but did not reduce the incidence of internal breakdown in ‘Laetitia’ plums cold stored for 60 days. Fruits in active MA, with perforated or non-perforated package, with CO2 absorber and LE, showed lower intensity of internal breakdown than CS.